ТҰЛҒА ҚАЛЫПТАСТЫРУДАҒЫ ҚЫЛМЫСТЫҚ САЯСАТТЫҢ РОЛІ (Journal of actual problems of jurisprudence, 2019)
In given article the role of a criminal policy in the course of formation of the person is considered.